Knowledge Management And Organizational Performance: A Research On Systematic Literature - Al Rashdi, Mubarak; Akmal, Suriati; Al-Shami, Samer Ali Hussein (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Studies that investigate the KM and organizational performance are few. The purpose of this study is to review the literature and review the articles related to the effect of knowledge management (KM) on organizational performance. A systematic literature review was conducted, and three screenings were performed to refine the articles. Article were extracted from Scopus and Web of Science (WoS). A total of 29 articles were considered to meet the selection criteria was reviewed, analyzed, and important information was extracted. A frequency analysis was conducted on these articles. The findings indicated that majority of the articles were extracted from WoS and published between 2015-2017 in Malaysia and Taiwan. The reviewed studies were conducted on manufacturing and technological industries using quantitative method. Sample size in most studies is less than 200 and data was analyzed using first generation of data analysis. Findings were discussed, and it was recommended for future studies to increase the sample size and use more frequently structural equation modeling.